2002
DOI: 10.1210/endo.143.6.8826
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel First Exon of Prolactin Receptor Gene Expressed in the Rat Brain

Abstract: A novel first exon, E1(4), whose sequence was distinct from those of the three known first exons, E1(1), E1(2), and E1(3), of the rat PRL receptor (PRL-R) gene was identified by cDNA cloning for the 5'-end region of PRL-R mRNA expressed in the rat brain. Sequence analysis revealed the presence of two different length E1(4) cDNAs. The longer cDNA contained the 243-bp E1(4) sequence, and the shorter cDNA lacked the 139-bp sequence at the 5'-end of the longer one. Neither E1(4) cDNA has a second exon sequence, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…We have previously demonstrated that the higher levels of PRL-R mRNA in the rat brain in late pregnancy and the following lactating period are dependent on the expression of E1 4 , Tanaka et al 2002. It has also been shown that the expression levels of PRL-R mRNA in the different brain regions are regulated by oestrogen, which increases the utilization of E1 2 and E1 3 first exons (Pi et al 2003).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…We have previously demonstrated that the higher levels of PRL-R mRNA in the rat brain in late pregnancy and the following lactating period are dependent on the expression of E1 4 , Tanaka et al 2002. It has also been shown that the expression levels of PRL-R mRNA in the different brain regions are regulated by oestrogen, which increases the utilization of E1 2 and E1 3 first exons (Pi et al 2003).…”
Section: Introductionmentioning
confidence: 95%
“…The 5 -end of the PRL-R cDNA was synthesized by the oligocapping method (Maruyama & Sugano 1994) as previously described (Tanaka et al 2002), cloned into pGEM-T Easy vector (Promega, Palo Alto, CA, USA) and sequenced.…”
Section: Animals and Hormone Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…in mammals, PRLR gene expression is regulated via the transcriptional activation of multiple alternative first exons that encode 5'-untranslated regions. Five first exons have been identified in the rat PRLR gene, i.e., E1 1 , E1 2 , E1 3 , E1 4 , and E1 5 [16,22,34,35]. the E1 1 variant of PRLR mRNA is expressed specifically in gonadal tissues [17], whereas the E1 2 variant is transcribed in the liver and kidney [22,35].…”
Section: Introductionmentioning
confidence: 99%
“…the E1 1 variant of PRLR mRNA is expressed specifically in gonadal tissues [17], whereas the E1 2 variant is transcribed in the liver and kidney [22,35]. the E1 3 variant is expressed generically in a wide range of tissues [18], whereas the E1 4 variant is expressed preferentially in the cerebrum, including the choroid plexus [27,34]. the E1 5 variant is transcribed in the brain, liver, and kidney [35].…”
Section: Introductionmentioning
confidence: 99%